A Clonal Complex 12 Methicillin-Resistant Staphylococcus aureus Strain, West Australian MRSA-59, Harbors a Novel Pseudo-SCCmec Element - Monecke, Stefan (Antimicrob Agents Chemother, 2015)
A West Australian methicillin-resistant Staphylococcus aureus strain (WA MRSA-59) was characterized by microarray and sequencing. Its pseudo-staphylococcal cassette chromosome mec (SCCmec) element comprised dcs, Q9XB68-dcs, mvaS-SCC, Q5HJW6, dru, ugpQ, ydeM, mecA-mecR-mecI, txbi mecI, tnp IS431, copA2-mco (copper resistance), ydhK, arsC-arsB-arsR (arsenic resistance), open reading frame PT43, and per-2. Recombinase genes, xylR (mecR2), and PSM-mec (phenol-soluble modulin) were absent. We suggest that mec complex A should be split into two subtypes. One harbors PSM-mec and xylR (mecR2). It is found in SCCmec types II, III, and VIII. The second subtype, described herein, is present in WA MRSA-59 and some coagulase-negative staphylococci.